Maternal Anemia, Nutrition, and Pregnancy Spacing as Determinants of Stunting: Anemia pada Ibu Hamil, Gizi, dan Jarak Antarkehamilan sebagai Faktor Penentu Stunting - Khasanah, Nur Riska Alfiyah; Azizah, Nurul; Rinata, Evi; Purwanti, Yanik (Indonesian Journal on Health Science and Medicine, 2025)
General Background: Stunting remains a major public health concern, particularly in Indonesia, where nutritional deficiencies and maternal conditions contribute significantly to its prevalence. Specific Background: Maternal anemia, chronic energy deficiency, and short pregnancy spacing are identified as major maternal factors influencing childhood stunting. Knowledge Gap: However, the combined role of these maternal factors in determining stunting among toddlers is still underexplored in regional contexts. Aims: This study aims to analyze the association between maternal anemia, nutritional status, and pregnancy spacing with stunting incidence among toddlers in Jabon Community Health Center. Results: A cross-sectional design involving 96 toddlers aged 24–59 months revealed significant associations through chi-square tests (p=0.000 for all variables). Logistic regression showed maternal anemia (p=0.000; OR=244.6) and short pregnancy spacing (p=0.003; OR=17.5) as strong predictors of stunting, while nutritional status showed no significant effect (p=0.107). Novelty: The study highlights anemia during pregnancy as the most dominant determinant, with a risk 244 times higher for producing stunted children. Implications: These findings emphasize the importance of anemia prevention and reproductive health education as key interventions to reduce stunting prevalence, suggesting that early maternal care and optimal pregnancy spacing should be prioritized in public health programs. Highlights: Maternal anemia is the strongest determinant of stunting Short pregnancy spacing significantly increases stunting risk Nutritional status showed no significant multivariate effect Keywords: Maternal Anemia, Pregnancy Spacing, Nutritional Status, Toddlers, Stunting